Risk Factors for Early Post-transplant Weight Changes Among Simultaneous Pancreas-kidney Recipients and Impact on Outcomes - Sandesh Parajuli, MD; Riccardo Tamburrini, MD, PhD; Fahad Aziz, MD; Ban Dodin, BS, MPhil; Brad C. Astor, PhD; Didier Mandelbrot, MD; Dixon Kaufman, MD, PhD; Jon Odorico, MD (Transplantation Direct)
Background. There are limited data about the risk factors for weight changes and the association of significant weight changes with graft and metabolic outcomes after simultaneous pancreas and kidney (SPK) transplantation. Methods. We included all SPK recipients with both allografts functioning for at least 6 mo post-transplant and categorized them based on the weight changes from baseline to 6 mo post-transplant. We analyzed risk factors for significant weight gain (SWG) and significant weight loss (SWL) over 6 mo post-transplant, as well as outcomes including pancreas uncensored graft failure, pancreas death-censored graft failure (DCGF), composite pancreas graft outcomes of DCGF, use of an antidiabetic agent, or hemoglobin A1C >6.5%, and kidney DCGF. Results. Of 280 SPK recipients, 153 (55%) experienced no significant weight change, 57 (20%) SWG, and 70 (25%) SWL. At 6 mo post-transplant, mean weight changes were 1.2% gain in the no significant weight change group, 13.4% gain in SWG, and 9.6% loss in the SWL groups. In multivariate analysis, the only factor associated with decreased risk for weight gain was older recipient age (aOR, 0.97; 95% confidence intervals, 0.95-0.99). Importantly, SWG or SWL were not associated with pancreas graft failure, P-DCGF, or K-DCGF. Interestingly in the adjusted model, SWG at 6 mo was associated with a lower risk for composite outcomes (HR, 0.35; 95% confidence intervals, 0.14-0.85). Conclusions. Forty-five percent of SPK recipients had significant weight changes by 6 mo post-transplant, but only 20% exhibited SWG. Likely because of proper management, weight changes were not associated with poor outcomes post-SPK transplant.